Factors Determining in The Selection of Pediatrics Health Care Service in Chennai, India - P, Yuvasri; P, Bharathwaj; K, Bincy; Palanisamy, Kaveri; VV, Anantharaman (National Journal of Community Medicine, 2024)
Background: Parents can choose their children's healthcare center; however, the healthcare business struggles to meet the growing health demands of vulnerable groups. Pediatricians now prioritize parental interests to improve their services and healthcare. This study also determined the association of sociodemographic variables with factors influencing the parent's decision. Materials and Methods: A cross-sectional study was undertaken among 146 parents of children aged 0 to 13 years who sought-patient services at a paediatrics department of a tertiary care center in Chennai between July 2023 to October 2023. The Validated semi structured questionnaire was administered. Results: In the present study, mean age group of the study population is 29±4, among them 69% were female and 31% were male. Sociodemographic variables, namely younger age, female gender, middle monthly income, and higher educational status, are influential in the parent's decision-making process for selecting a health care center. Conclusion: Although parents may lack the ability to assess all facets of care and treatment, their perspectives contribute immensely to the interpersonal aspect of care, communication, information, and care organization. The present study has yielded significant results that enhance the knowledge base of practitioners, managers, and other professionals tasked with delivering pediatrics general practice services.